Perancangan Bot Pada Discord Untuk Pengendali Aktuator di Raspberry Pi - Tatit Kisyaprakasa; Rizal Maulana; Hurriyatul Fitriyah (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Internet of things (IoT) is a relationship between machines, one of the well-known IoT is bot. In this research, a bot is designed that can be used with Raspberry Pi. Discord application is used and user can give a number of commands to the chat column so that the bot can run. In its implementation, 3 actuators used on bot and has performed all technical functions and every case thats can be done properly and successfully. In time measurement test using Stepper Motor 28BYJ-48, resulted average tambah command execution time is 334,14ms, the gerak command is 0,35ms and the hapus command is 1,04ms. When migrating using the Servo SG-90, it has an average tambah command execution time of 385,55ms, 0,33ms of gerak command, and 1,28ms in hapus command. In testing time using DC Motor the average execution time of the tambah command is 344,49ms, the gerak command is 0,33ms, and the hapus command is 1,22ms. The results of the average movement percentage error using the Stepper Motor 28BYJ-48 are 0,154%, the SG-90 Servo movement has a percentage of 0,991%, and the DC Motor rotation has a percentage of 28,02%.